ESPEN guidelines on chronic intestinal failure in adults. Issue 2 (April 2016) - Pironi, Loris; Arends, Jann; Bozzetti, Federico; Cuerda, Cristina; Gillanders, Lyn; Jeppesen, Palle Bekker; Joly, Francisca; Kelly, Darlene; Lal, Simon; Staun, Michael; Szczepanek, Kinga; Van Gossum, André; et al.
Summary: Background & aims: Chronic Intestinal Failure (CIF) is the long-lasting reduction of gut function, below the minimum necessary for the absorption of macronutrients and/or water and electrolytes, such that intravenous supplementation is required to maintain health and/or growth. CIF is the rarest organ failure. Home parenteral nutrition (HPN) is the primary treatment for CIF. No guidelines (GLs) have been developed that address the global management of CIF. These GLs have been devised to generate comprehensive recommendations for safe and effective management of adult patients with CIF. Methods: The GLs were developed by the Home Artificial Nutrition & Chronic Intestinal Failure Special Interest Group of ESPEN. The GRADE system was used for assigning strength of evidence. Recommendations were discussed, submitted to Delphi rounds, and accepted in an online survey of ESPEN members. Results: The following topics were addressed: management of HPN; parenteral nutrition formulation; intestinal rehabilitation, medical therapies, and non-transplant surgery, for short bowel syndrome, chronic intestinal pseudo-obstruction, and radiation enteritis; intestinal transplantation; prevention/treatment of CVC-related infection, CVC-related occlusion/thrombosis; intestinal failure-associated liver disease, gallbladder sludge and stones, renal failure and metabolic bone disease. Literature search provided 623 full papers. Only 12% were controlled studies or meta-analyses. A total of 112 recommendations are given: grade of evidence, very low for 51%, low for 39%, moderate for 8%, and high for 2%; strength of recommendation: strong for 63%, weak for 37%. Conclusions: CIF management requires complex technologies, multidisciplinary and multiprofessional activity, and expertise to care for both the underlying gastrointestinal disease and to provide HPN support. The rarity of the condition impairs the development of RCTs. As a consequence, most of the recommendations have a low or very low grade of evidence. However, two-thirds of the recommendations are considered strong. Specialized management and organization underpin these recommendations.